Bis(3,5-dinitrobenzoato-κO1)tetramethanolcobalt(II) - Bipasa Sarkar; Abhijit Roy; Seik Weng Ng; Edward R. T. Tiekink (Acta Crystallographica Section E, 2010)
The CoII atom (site symmetry overline{1}) in the title complex, [Co(C7H3N2O6)2(CH3OH)4], exists within an octahedral O6 donor set defined by two O-monodentate 3,5-dinitrobenzoate anions and four methanol O atoms. An intramolecular Om—H...Oc (m = methanol and c = carbonyl) hydrogen bond leads to the formation of an S(6) ring. In the crystal, centrosymmetrically related molecules associate via further Om—H...Oc hydrogen bonds, leading to linear supramolecular chains propagating along the a-axis direction.